Synthesis and Characterization of New Polymer from Bisacodyl A (Baghdad Science Journal, 2016)
A new series polymers was synthesized from reaction starting material Bisacodyl A or [(2-Pyridinylmethylene) di-4, 1-phenylene di acetate] with hydrogen bromide, then the products were polymerized by addition polymerization from used adipoyl and glutaroyl chloride. The structure of these compounds was characterized by FT-IR, melting points, TLC, X-Ray, DSC and 1H-NMR for starting material. These compounds were also screened for their antibacterial activists?